The Kansei Engineering Method for Determining the Emotional Design Concept of the Metaverse Library Interface: Technical University Students Perspectives - Nik Ahmad, Nik Azlina; Mohd Lokman, Anitawati; Abd Majid, Ezwan Shah; Hakim Suhaimi, Ahmad Iqbal (Journal of Technical Education and Training, 2025)
The rise of metaverse technology has impacted the way education is experienced through immersive interfaces, making user interface (UI) design a critical factor in shaping its emotional impact on users; the key to fostering engagement and satisfaction. However, providing emotion-centric UI that effectively satisfy user demands and technological competencies is an ongoing challenge. For that reason, this study examines the emotional responses from students of a technical university regarding metaverse library interfaces, aiming to identify the mapping correlation between UI design factors and the user-demanded experience. This experiment employed Kansei Engineering (KE) method, incorporating 28 specimens and 60 Kansei Words (KWs). Through the application of multivariate statistical analysis, the emotionally demanding UI concepts for the metaverse library were determined, with “radiance”, “orderliness”, and “conciseness” identified as the most significant (72.68%). Drawing from these findings, this study provides valuable guidance for improving user experience (UX) and shaping future design strategies of the metaverse libraries in technical universities. This research not only enhances emotional experience through UI design but also contributes to the growing importance of digital literacy in modern technical-based education and educational technology development, aligned with the goal of Technical and Vocational Education and Training (TVET).